Pengaruh Penetapan Harga dan Kualitas Produk Terhadap Tingkat Penjualan pada Usaha Ikan Kabupaten Takalar - Nabila Putri Retisa; Andi Rustam; Andi Arifwangsa Adiningrat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of pricing and product quality on sales levels in fish businesses at TPI Beba, Takalar Regency. This study uses a quantitative approach with a survey method by distributing questionnaires to 91 respondents who are fish business actors. The independent variables in this study are pricing and product quality, while the dependent variable is the sales level. Data analysis was carried out using multiple linear regression using SPSS. The results showed that pricing and product quality had a partial and simultaneous effect on sales levels. The right pricing and good product quality can significantly increase sales. This study provides important implications for fish business actors in designing pricing strategies and maintaining product quality to increase competitiveness and income.